Analisis Material Beton Bertulang Pasca Kebakaran dan Metode Perbaikan Elemen Strukturnya - Sulendra, I Ketut; Tatong, Burhan (Department of Civil Engineering, Diponegoro University, 2008)
Fire is often destroyed on building structures at any time. Fired caused to change physically and mechanically of properties of reinforced concrete building. Strength, stiffness and ductility of structures generally decrease and degradation after fired. Some method to estimate and assessment residual strength of reinforced structured after fired are very importat to research and to forensic engineering structure after fired. Estimated high temperature and duration of fired after fired by phenolphthalein indicator (PP-test), CaO-free test and Hammer Test. Values of concrete compression strength and tensil strength of reinforced estimate from field samples. Some samples are put by core drill apparatus to give cylendric concrete and testing by compression testing ubit. Some concrete beams to made and to give 400ºC, 600ºC, 800ºC and 1000ºC temperature to indicated middle and heavy destroyed after fired. Flexural and shear repairing to give to those beams. To found little to middle destroyed at GUDANG building and middle to heavy destroyed at PASAR INPRES MANONDA building after tst by by phenolphthalein indicator (PP-test), CaO-free test and Hammer Test. Concrete compression strength more than 50% decrease after 800ºC fired and more than 20% decrease reinforced tensil strength after fired at 1000ºC fired temperature indicated middle to heavy destroyed. Repairing by CFS to the beams give result only 63% flexural strength at 800ºC and 53% shear strength at 800ºC.If fired 400ºC to 600ºC fired temperature the repairedto the beams by CFS can increase flexural and shear strength more than intact beams.Keywords: Reinforced Concrete, Fire, RepairingPermalink: http://ejournal.undip.ac.id/index.php/mkts/article/view/3665[How to cite: Sulendra, I.K. dan Tatong, B. (2008), Analisis Material Beton Bertulang Pasca Kebakaran dan Metode Perbaikan Elemen Strukturnya, Jurnal Media Komunikasi Teknik Sipil, Tahun 16, No. 1, pp. 48-60]